Physiological Mechanism of Internode Bending Growth After the Excision of Shoot Sheath in Fargesia yunnanensis and Its Implications for Understanding the Rapid Growth of Bamboos - Wang, Shuguang; Zhan, Hui; Li, Pengcheng; Chu, Caihua; Li, Juan; Wang, Changming (Frontiers in Plant Science, 2020)
The physiological function of bamboo shoot sheaths is still unclear. In the present study, we investigated the anatomical and physiological influences of bamboo shoot sheaths on the internode elongation by striping longitudinally a part of sheaths. The internodes would bend towards the bare sides during a night. The results showed that amounts of water leaked at the cut of shoot sheaths during the night, which impeded the increase of water pressure, water and assimilate transport rates, and decreased starch and soluble sugar catabolism in the bare side of the internodes. Higher water pressure and sugar metabolism increased the vacuole expansion and promoted the cell expansion in the outer sides as compared to the bare sides. The bending growth of internodes was mainly due to the significant differences in cell expansion, which was led by the different water pressure and sugar hydrolysis levels between the inner and outer sides. Bamboo internode elongation mainly relied on the increase of water pressure and soluble sugar concentration. Shoot sheaths played an important role in the rapid growth of bamboo shoots as one controller in water and assimilate transportation. This study gave a new insight in understanding the rapid growth mechanism of bamboo plants.